Technique for Medial Meniscus Ramp Repair: An Anatomic Approach - Milind V. Pimprikar, M. S. D. Ortho. P. G. Dip. Sports and Exercise Medicine; Hitendra G. Patil, M.B.B.S., D.N.B. Ortho (Arthroscopy Techniques, 2024)
Medial meniscus ramp lesions are commonly associated with anterior cruciate ligament injury. They are one of the causes of positive pivot shift and can lead to failure to obtain rotary stability if missed during the surgical procedure. Several repair methods use a suture lasso from 2 posteromedial portals to attach the posteromedial capsule to the meniscus. Because it was concluded at the consensus meeting of the European Society for Sports Traumatology, Knee Surgery and Arthroscopy in 2019 that ramp lesions are not considered a meniscal tear and the lesion is essentially in either the articular capsule, meniscal capsular ligament, or meniscotibial ligament (MTL), it should be considered as a peel-off injury of the posteromedial capsule. This lesion is a meniscocapsular separation with or without MTL injury. Thus, reattaching the capsule and MTL to the bone on the posteromedial aspect would provide adequate anatomical repair. The prevailing repair methods suture the capsule to the meniscus, ignoring the MTL attachment. This technique addresses the refixation of the meniscal capsular ligament and MTL to the bone where it is attached instead of suturing it to the meniscus, thus providing sounder anatomical repair.